2018
DOI: 10.1021/acs.jafc.8b03398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for Improving Emulsification Efficiency of Soy Glycinin by Glycation with Soy Soluble Polysaccharide

Abstract: Glycation with carbohydrates has been considered to be an effective strategy to improve the emulsifying properties of plant storage globulins, but the knowledge is inconsistent and even contradictory. This work reported that the glycation with soy soluble polysaccharide (SSPS) progressively improved the emulsification efficiency of soy glycinin (SG) in a degree-of-glycation (DG)-dependent manner. The glycation occurred in both the acidic (A) and basic (B) polypeptides to a similar extent. The physicochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 49 publications
(113 reference statements)
1
13
0
1
Order By: Relevance
“…whey protein microgels (Destribats, et al, 2014;Sarkar, et al, 2016b) and lactoferrin nanoparticles or nanogels (David-Birman, et al, 2013;Gal, et al, 2013;Meshulam, et al, 2014;Sarkar, et al, 2018), those involving particles obtained from plant proteins are fairly recent and are attracting significant research attention. For example, Liu and co-authors (Liu, et al, 2017;Liu, et al, 2013;Liu, et al, 2014;Liu, et al, 2016;Peng, et al, 2020;Peng, et al, 2018;Zhu, et al, 2017) investigated the ability of soy protein nanoparticles aggregates (SPN) (~ 100 nm, created via heat-treatment at 95 o C for 15 min) to act as Pickering stabilizers. On the other hand, Chen, et al (2014) prepared heat denatured soy protein nanogel particles at various pH values (pH 2.0-7.0) and added ions (0-200 mM NaCl).…”
Section: Introductionmentioning
confidence: 99%
“…whey protein microgels (Destribats, et al, 2014;Sarkar, et al, 2016b) and lactoferrin nanoparticles or nanogels (David-Birman, et al, 2013;Gal, et al, 2013;Meshulam, et al, 2014;Sarkar, et al, 2018), those involving particles obtained from plant proteins are fairly recent and are attracting significant research attention. For example, Liu and co-authors (Liu, et al, 2017;Liu, et al, 2013;Liu, et al, 2014;Liu, et al, 2016;Peng, et al, 2020;Peng, et al, 2018;Zhu, et al, 2017) investigated the ability of soy protein nanoparticles aggregates (SPN) (~ 100 nm, created via heat-treatment at 95 o C for 15 min) to act as Pickering stabilizers. On the other hand, Chen, et al (2014) prepared heat denatured soy protein nanogel particles at various pH values (pH 2.0-7.0) and added ions (0-200 mM NaCl).…”
Section: Introductionmentioning
confidence: 99%
“…The far-UV CD spectra and secondary structure distribution of WPH, W-S-L, and W-L-S are presented in Figure . The spectrum of WPH, exhibiting a remarkable negative band at ∼200 nm and a peripheral shoulder band at ∼230 nm, revealed the fact that the secondary structure of WPH was mainly composed of β-sheet (37.6 ± 0.14%) and random coil (43.7 ± 0.29%) . A significant hypsochromic shift in the spectrum of W-S-L and W-L-S indicated that the structure of WPH was changed after modification.…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of WPH, exhibiting a remarkable negative band at ∼200 nm and a peripheral shoulder band at ∼230 nm, revealed the fact that the secondary structure of WPH was mainly composed of β-sheet (37.6 ± 0.14%) and random coil (43.7 ± 0.29%). 17 A significant hypsochromic shift in the spectrum of W-S-L and W-L-S indicated that the structure of WPH was changed after modification. As shown in the inset of Figure 2, the contents of α-helix, β-sheet, β-turn, and random coil were 7.1%, 11.9%, 34.8%, and 46.2% for W-S-L and 6.4%, 18.4%, 30.4%, and 44.8% for W-L-S, respectively, which indicated that the order of the two modification methods resulted in a different effect on the secondary structure of WPH because of the various degrees of reaction with LD and SA for modified WPH after succinylation and glycation in different orders.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, they exhibit poor emulsifying capability compared to milk derived proteins such as casein or whey protein, due to their large molecular weight, compact globular structure and limited solubility (Dickinson, 2019;Tang, 2017). Recent progress on achieving emulsifiers from SPI and SPI derived materials has mainly focused on Pickering-type aggregated protein emulsifiers or microgel particles (Chen, Chen, Ren, & Zhao, 2011a;Dickinson, 2019;Guo, et al, 2016;Hao, Peng, & Tang, 2020;Luo, Liu, & Tang, 2013;Matsumiya & Murray, 2016;Peng, Xu, Liu, & Tang, 2018;Tang, 2017). These reported emulsions are not stabilised by molecularly adsorbed protein layers (i.e.…”
Section: Introductionmentioning
confidence: 99%